2020
DOI: 10.1080/13548506.2020.1858489
|View full text |Cite
|
Sign up to set email alerts
|

Psychological status of TMD patients, orthodontic patients and the general population during the COVID-19 pandemic

Abstract: Confronting the outbreak of COVID-19, this cross-sectional study was aimed to assess psychological status of temporomandibular disorders (TMD) patients, orthodontic patients and the general population in China during the pandemic. An online anonymous questionnaire was developed in Chinese, including the individual background information, the perception of the epidemic, and level of anxiety and depression through Kessler Psychological Distress Scale (K10). The respondents were divided into ORTHO group, TMD grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
29
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 38 publications
6
29
3
Order By: Relevance
“…Women have been reported to undergo greater psychological disturbances than men, 1,4 in contrast to the results of the present study. The variations in the results may be related to the differences in the number of participants among studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Women have been reported to undergo greater psychological disturbances than men, 1,4 in contrast to the results of the present study. The variations in the results may be related to the differences in the number of participants among studies.…”
Section: Discussioncontrasting
confidence: 99%
“…A few studies have related to TMDs and anxiety in individuals during the COVID-19 pandemic, 3,4,29 but the authors are unaware of a previous study comparing the anxiety levels in patients diagnosed with masticatory muscle pain before and during the COVID-19 pandemic. The null hypothesis was rejected as COVID-19 had a strong association with anxiety in patients who were already suffering from masticatory muscle pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been extensively adopted to evaluate the anxiety of patients in the dental and medical fields [ 2 , 15 , 19 ]. Introduced in the annual US National Health Interview Survey [ 8 ], translated into eleven different languages [ 46 , 47 ], and used as a screening tool for mental disorders in various situations [ 46 , 48 , 49 ] made it among the most reliable and valid tools to assess the psychological impact of the pandemic on orthodontic patients [ 19 , 50 ]. Given its widespread utilization in survey research methodologies, we sought to integrate this tool in our survey design.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Kessler Scale (K10) , Xiong et al [ 19 ] evaluated the mental health of orthodontic patients in China during the early phases of the pandemic and found that over one-third of the patients experienced mental distress. Earlier, Wu et al [ 50 ] compared the psychological status between temporomandibular disorders (TMD), orthodontic patients, and the general population and concluded that TMD patients had a higher level of anxiety than the other two groups during the pandemic in China. Moreover, in another attempt to evaluate the impact of coronavirus pandemic on orthodontic appointments and orthodontic patients’ anxiety without the use of the Kessler Scale (K10), Cortin et al [ 15 ] showed that patients willing to attend an orthodontic appointment had a lower level of anxiety than those who would not go.…”
Section: Discussionmentioning
confidence: 99%